Of all creatures itchy and small - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Insect Pest Management By D Dent, CABI Bioscience, 2000. 432 pp. ISBN 0851993419 GBP 27.50 Euro 43.15